# Problem of the Week #20 - August 13th, 2012

Status
Not open for further replies.

#### Chris L T521

##### Well-known member
Staff member
Thanks to those who participated in last week's POTW!! Here's this week's problem!

-----

Problem: Suppose that $\displaystyle g(t) = \int_0^t f(\tau)\,d\tau$. If $G(s)$ and $F(s)$ are the Laplace transforms of $g(t)$ and $f(t)$ respectively, show that $G(s) = \dfrac{F(s)}{s}$.

Recall that $\displaystyle F(s) = \mathcal{L}\{f(t)\} = \int_0^{\infty} e^{-st}f(t)\,dt$.

-----

#### Chris L T521

##### Well-known member
Staff member

Sudharaka's solution:

$g(t) = \int_0^t f(\tau)\,d\tau$

\begin{eqnarray}

G(s)&=&\mathcal{L}\{g(t)\}\\

&=&\int_0^{\infty} e^{-st}\int_0^t f(\tau)\,d\tau\,dt\\

&=&\int_0^{\infty}\int_{0}^{t}e^{-st}f(\tau)\,d\tau\,dt

\end{eqnarray}

Note that, $$0<\tau<t<\infty$$. Changing the order of integration we get,

\begin{eqnarray}

G(s)&=&\int_0^{\infty}\int_{\tau}^{\infty}e^{-st}f(\tau)\,dt\,d\tau\\

&=&\int_0^{\infty}f(\tau)\int_{\tau}^{\infty}e^{-st}\,dt\,d\tau\\

&=&\int_0^{\infty}f(\tau)\frac{e^{-s\tau}}{s}\,d\tau\\

&=&\frac{1}{s}\int_0^{\infty}e^{-s\tau}f(\tau)\,d\tau\\

\therefore G(s)=\frac{F(s)}{s}

\end{eqnarray}

Let's consider the laplace transform of $g(t)$

$$G(s)=\mathcal{L}\{g(t)\}=\int_0^\infty e^{-st}g(t)\, dt$$

since, $g(t)=\displaystyle \int_0^t f(\tau )\, d\tau$

\begin{align*} \mathcal{L}\{g(t)\}&=\int \limits_0^\infty e^{-st}g(t)\, dt \\ &=\int \limits_0^\infty e^{-st}\left[ \int_0^t f(\tau )\, d\tau \right] dt \\ &=\int \limits_{0}^{\infty}\int \limits_{0}^{t} e^{-st}f(\tau )\, d\tau dt\\ \end{align*}

By switching variables, the boundaries of $t$ and $\tau$ changes as,

$0<\tau<\infty$ and $\,\tau<t<\infty$

then,

$$\mathcal{L}\{g(t)\}=\int \limits_0^\infty \int \limits_\tau^\infty e^{-st}f(\tau )\, dtd\tau$$

since $f(\tau )$ is independent on $t$,

\begin{align*} \mathcal{L}\{g(t)\}&=\int \limits_{0}^{\infty}f(\tau )\left[ \int \limits_\tau^\infty e^{-st}\,dt \right] d\tau \\ &=\int \limits_0^\infty f(\tau ) \left[ \frac{e^{-st}}{-s}\right] _\tau^\infty \,d\tau \\ &=\int \limits_0^\infty f(\tau ) \left[ \frac{0-e^{-s\tau }}{-s}\right] \,d\tau (when s>0) \\&=\frac\int \limits_0^\infty f(\tau ) e^{-s\tau }\,d\tau }{s}\\ &=\frac\int \limits_0^\infty f(t) e^{-st }\,dt }{s}\\ &=\frac{F(s)}{s} \end{align*

$$\therefore \; G(s)=\frac{F(s)}{s}$$ for $s>0$

Status
Not open for further replies.